The Existence of Wage Rules to Increase the Needs of a Just Living According to the Perspective of Maqashid Al-Sharia - Edi Sahputra Siregar (Budapest International Research and Critics University, 2022)
The components of the necessities of life that are used as a reference in determining the minimum wage in Indonesia have changed 4 times. This change occurs because adjusting to the development of needs was previously considered less important but has now become important. In Islam there are 5 basic elements of human needs that must be met or known as maqasid shari'ah. The five main elements of maqasid shari'ah are divided into 3 categories, namely:Daruriyyah, Hajjiyah, andTahsiniyyah. This study examines how the components of the necessities of life in the regulation of minimum wages in the maqasid shari'ah perspective. This study concludes that the development of the necessities of life which is used as a guide in determining the minimum wage has taken into account the level of living needs. Most of the components of the Decent Living Needs (KHL) are in the daruriyyah and hajjiyah areas, very few are classified as tahsiniyyah. The addition of the component quota and the improvement in the quality of the components are evidence that there is attention to the level of need starting from the daruriyyah first and then the hajjiyah and then the tahsiniyyah. This change indicates a change in the law in accordance with the development of the situation.